2015
DOI: 10.1063/1.4905230
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and quasilinear theory of proton firehose instability

Abstract: The electromagnetic proton firehose instability is driven by excessive parallel temperature anisotropy, T∥ > T⊥ (or more precisely, parallel pressure anisotropy, P∥ > P⊥) in high-beta plasmas. Together with kinetic instabilities driven by excessive perpendicular temperature anisotropy, namely, electromagnetic proton cyclotron and mirror instabilities, its role in providing the upper limit for the temperature anisotropy in the solar wind is well-known. A recent Letter [Seough et al., Phys. Rev. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 44 publications
6
43
0
Order By: Relevance
“…The firehose modes' evolution is governed by Δp [12], which varies in space. Near the wave nodes, where S ¼ j∇uj ≈ 0 and δB z ≈ 0, Δp is not driven by a large-scale dB=dt and can freely decay [29,32,34,35]. Near the wave antinodes, where S ∼ β −1=2 ω A ≈ 6 × 10 −5 Ω i [10] and δB z ≠ 0, Δp is continuously driven by the decreasing field [29,31,[36][37][38].…”
mentioning
confidence: 99%
“…The firehose modes' evolution is governed by Δp [12], which varies in space. Near the wave nodes, where S ¼ j∇uj ≈ 0 and δB z ≈ 0, Δp is not driven by a large-scale dB=dt and can freely decay [29,32,34,35]. Near the wave antinodes, where S ∼ β −1=2 ω A ≈ 6 × 10 −5 Ω i [10] and δB z ≠ 0, Δp is continuously driven by the decreasing field [29,31,[36][37][38].…”
mentioning
confidence: 99%
“…Four different initial conditions are indicated in different colors and also labeled. Time evolution of the perpendicular and parallel betas, temperature ratio, and wave energy density are plotted as a function of normalized time order to test whether such an assumption is valid we have carried out onedimensional particle-in-cell simulations (Seough et al , 2015a. We found that the agreement between the simplified quasilinear theory and PIC simulation is quite good in the case of proton-cyclotron instability, but for parallel proton firehose instability the agreement became poorer.…”
Section: Validity Of Quasilinear Moment Theorymentioning
confidence: 99%
“…This contributes to the distortion of the initial biMaxwellian form into a dumb-bell shape distribution (Astfalk and Jenko 2017), and leads to the premature quenching of the instability. The time evolution of the initially bi-Maxwellian distribution in PIC code runs is discussed in Seough et al ( , 2015a, and shows that indeed, for EMIC case, the quasi-bi-Maxwellian shape is maintained throughout most of the simulation time. In contrast, for PFH case, the bi-Maxwellian form gets distorted quite early on, even though later on, the quasi-bi-Maxwellian shape appears to be restored.…”
Section: Validity Of Quasilinear Moment Theorymentioning
confidence: 99%
See 2 more Smart Citations